Acute and long-term exercise adaptation of adipose tissue and skeletal muscle in humans: a matched transcriptomics approach after 8-week training-intervention - Dreher, Simon I.; Irmler, Martin; Pivovarova-Ramich, Olga; Kessler, Katharina; Jürchott, Karsten; Sticht, Carsten; Fritsche, Louise; Schneeweiss, Patrick; Machann, Jürgen; Pfeiffer, Andreas F. H.; Hrabě de Angelis, Martin; Beckers, Johannes; et al. (International Journal of Obesity, 2023)
Background Exercise exerts many health benefits by directly inducing molecular alterations in physically utilized skeletal muscle. Molecular adaptations of subcutaneous adipose tissue (SCAT) might also contribute to the prevention of metabolic diseases. Aim To characterize the response of human SCAT based on changes in transcripts and mitochondrial respiration to acute and repeated bouts of exercise in comparison to skeletal muscle. Methods Sedentary participants (27 ± 4 yrs) with overweight or obesity underwent 8-week supervised endurance exercise 3×1h/week at 80% VO2peak. Before, 60 min after the first and last exercise bout and 5 days post intervention, biopsies were taken for transcriptomic analyses and high-resolution respirometry ( n = 14, 8 female/6 male). Results In SCAT, we found 37 acutely regulated transcripts (FC > 1.2, FDR < 10%) after the first exercise bout compared to 394, respectively, in skeletal muscle. Regulation of only 5 transcripts overlapped between tissues highlighting their differential response. Upstream and enrichment analyses revealed reduced transcripts of lipid uptake, storage and lipogenesis directly after exercise in SCAT and point to β-adrenergic regulation as potential major driver. The data also suggest an exercise-induced modulation of the circadian clock in SCAT. Neither term was associated with transcriptomic changes in skeletal muscle. No evidence for beigeing/browning was found in SCAT along with unchanged respiration. Conclusions Adipose tissue responds completely distinct from adaptations of skeletal muscle to exercise. The acute and repeated reduction in transcripts of lipid storage and lipogenesis, interconnected with a modulated circadian rhythm, can counteract metabolic syndrome progression toward diabetes. New & noteworthy Transcriptional alterations demonstrate that adipose tissue responded to exercise completely distinct from skeletal muscle in the same human subjects. Adipose tissue showed acute and repeated reduction in transcripts of lipid uptake, synthesis and storage. The data also suggest the restoration of a healthier circadian rhythm in adipose tissue of subjects with obesity after regularly performed exercise. The interconnection of circadian rhythm with lipid metabolism possibly contributes to improved metabolic health and prevention of diabetes.